PSYCHO-EMOTIONAL ADDICTION FACTORS FROM THE RESTORATION OF REPRODUCTIVE FUNCTION IN NURSING MOTHERS (Academia Science Repository, 2023)
We observed 40 lactating women who had undergone physiological childbirth. Restoration of menstrual function after normal childbirth in nursing mothers after 1.5-5 months occurs in 60% of cases. Lactational amenorrhea for 6-12 months or more after normal delivery occurs in 27.5% of women. The high incidence (27.5%) of unplanned pregnancies in nursing mothers during the first year after normal childbirth indicates the need to use contraceptives immediately after childbirth.